Face-Saving and Face-Threatening Strategies in Sundanese Teenagers' Interactions through TikTok Content - Mustaam Firmansyah, Luki Alifia; Mujani, Sahril; Pujiani, lilik (STIBA IEC JAKARTA, 2025)
In today’s digital landscape, traditional norms of politeness are increasingly challenged by the fluid and often informal nature of online communication, particularly among teenagers. This study focuses on how Sundanese teenagers apply undak-usuk basa, a cultural system of linguistic politeness in their content interactions on TikTok, a platform characterized by spontaneous and casual exchanges. The aim of this research is to analyze how face-saving and face-threatening strategies are utilized by Sundanese-speaking adolescents in digital peer communication. Employing a qualitative approach, the study collects data through observation and discourse analysis of selected TikTok videos. Brown and Levinson’s Politeness Theory serves as the primary framework to examine how traditional politeness strategies are adapted within modern teenage interactions. The findings reveal that Sundanese teenagers apply undak-usuk basa selectively, influenced by social context, peer dynamics, and platform-specific norms. These results suggest that while digital media shapes communication behavior, the cultural norms embedded in undak-usuk basa remain relevant in the practice of both face-saving and face-threatening acts